Numerical integration of lattice rotation in polycrystal plasticity - Kok, S.; Beaudoin, A. J.; Tortorelli, D. A. (International journal for numerical methods in engineering, 2001)
A numerical algorithm to calculate the lattice rotation in polycrystal plasticity models, that is based on the analytical integration of the lattice rotation update equation, is presented. Implicit and explicit implementations perform equally well and are superior to the currently used numerical integration schemes. Copyright © 2001 John Wiley & Sons, Ltd.